PolydetectTM - Polygraphic Method for Counterproductive Behavior Index Profiling - Hashim Bin Hj Yusoff; Ahmad Zaki Abu Bakar; Rose Alinda Alias (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2007)
Various tools have been utilized to help detect counterproductive behaviors including the use of penciland papers methods and polygraph techniques. The purpose of this paper is to study, design and develop aproof-of-concept polygraphic method for counterproductive behavior index profiling system for human resourceselection besides building and developing polygraphic repository of counterproductive behavior index profile.10 major areas are covered namely alcohol use, computer abuse, credibility, customer service, fundamentaldata, illegal drug use, sexual harassment, theft propensity, work attitude, and work history. Main advantages: 3major areas of concerns, namely little or no concerns (Angel) for lower scorers of 0-33, normal concerns(Human) for medium scorers of 34-55 and serious concerns (Devil) for higher scores of 56-100 are developedwith the ability of producing radar charts for each areas of concern. American Polygraph Association memberstrained as Polygraph Examiners shall be the primary user of this system for pre employment purposes andemployment screening. It also facilitates human resources department for personnel selection. This researchfocuses on the Axciton™ and Lafayette™ polygraph instruments that use the PolyScore algorithms anddevelopment of Polygraphic Method for Counterproductive Behavior Index Profiling System –POLYDETECTTM. Information System Research Design Framework and Multiple Perspective Framework arebeing utilized for the purpose.Keywords: Polygraph, Counterproductive Behavior Index Profiling, Repositories, Information System DesignResearch Framework, Multiple Perspective Framework.